2015
DOI: 10.1093/ecco-jcc/jjv225
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab to Treat Refractory Inflammation After Pelvic Pouch Surgery for Ulcerative Colitis

Abstract: Infliximab can effectively treat inflammatory pouch complications. Pre-treatment mPDAI <10 and early endoscopy may identify responders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 36 publications
0
22
0
6
Order By: Relevance
“…We then measured TpH-1 and SERT expression in the pouch biopsies cultured ex vivo with infliximab, an anti-TNF-α monoclonal antibody that has been demonstrated to exert a therapeutic effect on patients with pouchitis. 33 Nonetheless, infliximab did not modify TpH-1 and SERT levels. In order to validate our ex vivo experiments, in the biopsy culture supernatants we detected IL-6, a cytokine of the innate immunity, and IL-8, a chemokine, known to be increased in pouch mucosa.…”
Section: Discussionmentioning
confidence: 93%
“…We then measured TpH-1 and SERT expression in the pouch biopsies cultured ex vivo with infliximab, an anti-TNF-α monoclonal antibody that has been demonstrated to exert a therapeutic effect on patients with pouchitis. 33 Nonetheless, infliximab did not modify TpH-1 and SERT levels. In order to validate our ex vivo experiments, in the biopsy culture supernatants we detected IL-6, a cytokine of the innate immunity, and IL-8, a chemokine, known to be increased in pouch mucosa.…”
Section: Discussionmentioning
confidence: 93%
“…Post-induction response was achieved in 74 % and long-term response in 62.6 %. Mean PDAI and CRP values showed a statistically significant decrease under therapy [668].…”
Section: Introductionmentioning
confidence: 90%
“…Two double-blind, placebo-controlled studies have demonstrated that VSL#3 is effective to maintain remission after induction with combination antibiotic therapies. 65,66 If a combination of oral antibiotics fail to induce or maintain remission, oral or topical mesalamine, corticosteroids, 67 anti-TNF drugs including infliximab [68][69][70][71] and adalimumab 72,73 are shown to be effective for chronic pouchitis. 74,75 According to a recent meta-analysis regarding the efficacy of anti-TNF therapy on chronic refractory pouchitis, the rates of short-term (8 weeks) and long-term (12 months) clinical remission were 0.10 (95% CI, 0.00-0.35) and 0.37 (95% CI, 0.14-0.62), respectively.…”
Section: Chronic Pouchitismentioning
confidence: 99%